Effect of foliar application of iron and ascorbic acid on growth and production of peach trees (Prunus Persica. L. cv. May Crest) - ديب , علي; صهيوني, فهد; توكلنا, محاسن; يوسف, يحيى (Latakia University Journal -Biological Sciences Series, 2020)
The experience was performed during 2018-2019 in (Bhozy/Tartous) in a peach orchard aged of 9 years to study the effect of foliar application of 500 mg/l (Fe-EDTA 13%), 500 mg/l(Feso4,7H2o), and 500 mg/l Ascorbic acid (AsA), separately or together (Fe-EDTA+ AsA), (Feso4,7H2O + AsA), the results showed that, foliar application of Fe-EDTA or Feso4 and AsA improved vegetative growth and fruits yield and quality compared to the control.